The planning and execution of ER-2 and DC-8 aircraft flights over Antarctica, August and September 1987 - Tuck, A. F.; Watson, R. T.; Condon, E. P.; Toon, O. B.; Margitan, J. J. (1989)
The significant ozone loss in the lower stratosphere over Antarctica during recent austral springs was studied by instrumented ER-2 and DC-8 aircraft. Data on the homogeneous gas composition, polar stratospheric clouds, and on tracers for dynamic motion are provided. The mission design is described, the aircraft and their payloads are documented, and the flight tracks are specified.